Pembentukan Moral Remaja melalui Teori Habitus Pierre Bourdieu dalam Perspektif Psikologi Pendidikan Islam - Siti Khusniatul Amanah; Istingadah Istingadah (Journal of Transdisciplinary Studies in Religion and Education, 2025)
The purpose of this study is to analyze the moral formation of adolescents through Pierre Bourdieu's habitus theory from the perspective of Islamic Educational Psychology. This study uses a qualitative method with a literature study approach, which examines the concepts of habitus, capital, and domain according to Bourdieu as well as Islamic educational literature on value habituation, role models, and supervision (muroqabah). The results show that the moral formation of adolescents occurs through repeated social interactions until they are internalized within them. If adolescents' habitus is formed by an environment that is permissive of violence and negative content, deviant behavior is more likely to emerge. Conversely, an Islamic habitus based on faith, noble morals, and the habituation of worship can strengthen adolescents' moral control and encourage the creation of positive behavior. Thus, the integration of habitus theory with the perspective of Islamic Educational Psychology can provide a comprehensive framework for formulating strategies for adolescent moral education in the era of globalization.